The Effect of Combination of Worm and Feed Towards Growth And Survival Rate of Giant Prawns (Macrobrachium rosenbergii) in the Recirculation System - Henny Maria Sinaga; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on March 30th-May 19th, 2019 in the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The aim of this study is to determine the effect of combination of worm and feed on the growth of giant prawns. The container of this research used a 60x40x40 cm 3 aquarium with 20 aquariums with a stocking density of 15 prawns/aquarium. This study used a Completely Randomized Design (CRD) with one factor of five treatment levels and three replications. Each treatment was given the combination of worm and feed as much as P0 (100% feed), P1 (75% feed and 25% worm), P2 (50% feed and 50% worm), P3 (25% feed and 75% worm), and P4 (100% worm). The results of the research showed that the best treatment was found in P2 (50% feed and 50% worm) feed resulting in absolute growthweight of 0,92 g, specific growth rate of 8,45%, feed efficiency of 95,20% and survival rate of 95,5%.Keywords : Macrobrachiumrosenbergii, combined of feed and worm, Growth